The Influence of Online Customer Review and Perceived Risk on E-Trust and Purchase Intention on E-Commerce Lazada in Pekanbaru City - Helfiyana, Helfiyana; Alwie, Alvi Furwanti; Samsir, Samsir (InJEBA : International Journal of Economics, Business and Accounting, 2024)
This study aims to determine The Influence of Online Customer Review and Perceived Risk on E-Trust and Purchase Intention on E-Commerce Lazada in Pekanbaru City. Primary data was collected by questionnare and hypothesis testing was conducted using Structural Equation Modelling – Partial Least Square (SEM – PLS) method with software SmartPLS version 4 program. Technique sampling was carried out by purposive sampling method with total of 180 respondents were selected based on certain criteria. The result of this study showed that online customer review has a significant effect on perceived risk, online customer review and perceived risk has a significant effect on e-trust, online customer review has a positive but not significant effect on purchase intention, perceived risk and e-trust has a significant effect on purchase intention. This result also showed that online customer review and perceived risk has a positive and significant effect on purchase intention with mediation of e-trust as an intervening variabel on e-commerce Lazada in Pekanbaru City.